Relationship of High Stress with Hypertension in Adults: Meta Analysis - Siti Luluk Khamidahtun Ni'mah; Sukma Sukma (Masters Program in Public Health, 2022)
Background: Hypertension is a condition that causes a person to experience a drastic increase in blood pressure. Hypertension is often referred to as the silent killer because it can damage target organs such as the brain, eyes, kidneys, heart and arteries. Based on the cause, the increase in blood pressure can occur due to essential or primary hypertension such as high stress. The aim of this study was to estimate the relationship between high stress and hypertension in adults, with a meta-analysis of the primary study conducted by the previous authors. Subjects and Method: This study is a meta-analysis using the PICO ie, population: adults; Intervention: high stress; Comparison: low stress; Result: hypertension. The articles used in this study were obtained from two databases, namely Pubmed and Google scholar. The keywords in the article search were “adults” AND “high stress” AND “low stress” AND “hypertension” cross-sectional or “Stress” AND “hypertension”. The included article is in full English with a cross-sectional study design for 2014 to 2021 and reports the adjusted odds ratio (aOR) in a multivariate analysis. Article selection using PRISMA flow chart. Article analysis using the Review Manager 5.3 application. Results: 10 articles with a cross sectional study involving 3,436 adults from 4 continents namely Asia, Europe, Africa and America to be used as a systematic review and meta-analysis. The data collected showed that high stress had a relationship with the occurrence of hypertension in adults as much as 1.66 times compared to adults with low stress (aOR=1.66; 95%CI= 1.28 to 2.17; p= 0.002). Conclusion: High stress has a relationship with hypertension in adults. Keywords: adults, high stress, hypertension Correspondence: Siti Luluk Khamidahtun Ni’mah. District Health Office of Ponorogo. Jl. Basuki Rahmad, Ponorogo, East Java, Indonesia. Email: lulupanma@gmail.com. Mobile: 08562563503.